2020
DOI: 10.1007/s00262-020-02734-1
|View full text |Cite
|
Sign up to set email alerts
|

Microwave ablation enhances tumor-specific immune response in patients with hepatocellular carcinoma

Abstract: Thermal ablative therapies are standard treatments for localized hepatocellular carcinoma (HCC). In addition to local tumor destruction, ablation leads to abscopal effects in distant lesions most likely mediated by an anti-tumor immune response. Although microwave ablation (MWA) is increasingly substituting other ablative techniques, its systemic immunostimulatory effects are poorly studied. We analyzed tumor-specific immune responses in peripheral blood of HCC patients after thermal ablation with regard to T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 42 publications
1
71
0
Order By: Relevance
“…Studies that show an increase in tumor specific lymphocytes in secondary lymphoid organs or in peripheral blood have also established the correlation between these activated cells and systemic decreases in tumor burden (28)(29)(30)(31). More recently, additional studies have also defined B cell activation, the maintenance of plasma cells, and even the generation of tumor specific antibodies following local tumor ablation and dendritic cell activation (29,31). For example, a study treating hepatocellular carcinoma with RFA reported that only 91 of the 178 patients that had a decreased neutrophil-to-lymphocyte ratio, which is an often used biomarker of systemic immune system activation, independently correlated to a significantly increased survival when compared to patients that did not see the increased ratio (32).…”
Section: The Role Of Ablation In Immunomodulationmentioning
confidence: 94%
See 1 more Smart Citation
“…Studies that show an increase in tumor specific lymphocytes in secondary lymphoid organs or in peripheral blood have also established the correlation between these activated cells and systemic decreases in tumor burden (28)(29)(30)(31). More recently, additional studies have also defined B cell activation, the maintenance of plasma cells, and even the generation of tumor specific antibodies following local tumor ablation and dendritic cell activation (29,31). For example, a study treating hepatocellular carcinoma with RFA reported that only 91 of the 178 patients that had a decreased neutrophil-to-lymphocyte ratio, which is an often used biomarker of systemic immune system activation, independently correlated to a significantly increased survival when compared to patients that did not see the increased ratio (32).…”
Section: The Role Of Ablation In Immunomodulationmentioning
confidence: 94%
“…Once in the lymphoid tissues, the dendritic cells present the antigens through MHC class I or class II receptors to naïve CD4+ and CD8+ T cells, respectively, along with co-stimulation of CD28 with CD80/86. Studies that show an increase in tumor specific lymphocytes in secondary lymphoid organs or in peripheral blood have also established the correlation between these activated cells and systemic decreases in tumor burden (28)(29)(30)(31). More recently, additional studies have also defined B cell activation, the maintenance of plasma cells, and even the generation of tumor specific antibodies following local tumor ablation and dendritic cell activation (29,31).…”
Section: The Role Of Ablation In Immunomodulationmentioning
confidence: 96%
“…Microwave ablation in HCC patients leads to abscopal effects in distant lesions reflected by enhanced tumor antigen specific T cell IFN-γ production that correlated with long term survival. These studies provide additional evidence for the potential synergistic effect that could be achieved by combination of local ablation and immunotherapeutic strategies against this challenging disease [128]. The above studies indicate that immune cell therapy is effective in reducing the recurrence rate, which is typically high for HCC patients following curative treatment.…”
Section: T Cells-based Immunotherapy Of Hccmentioning
confidence: 78%
“…[218,219] Higher temperatures have been suggested as more efficient at instigating anti-tumor immune responses as they are more prolific at inducing immunogenic cell death, [220] although in vivo studies have repeatedly confirmed that 42°C for 30 min is effective for inducing significant DAMP expression. [221][222][223] A number of reports have described adaptive responses with thermal ablation as a monotherapy via similar mechanisms to hyperthermia; [219,224] however, in the majority of cases, ablative therapies only achieve durable antitumor immune responses when applied in combination with immunotherapies. [218,225] Therefore, based on the literature described, adaptive immunity can indeed be induced by moderate hyperthermia and the HSP70 family appear to be one of the principal sources of this response.…”
Section: Adaptive Immunitymentioning
confidence: 99%